Targeting the chemokine receptor CXCR4 for cancer therapies - Ariana Rueda; Naroa Serna; Ramon Mangues; Antonio Villaverde; Ugutz Unzueta (Biomarker Research)
Abstract The C-X-C chemokine receptor type 4 (CXCR4) has emerged as a key molecular biomarker for cancer therapies due to its critical role in tumor progression and metastases by displaying a stem cells phenotype. Its overexpression has been observed in more than 20 types of cancers, including solid tumors and hematological malignancies, and it is often associated with tumor aggressiveness and poor prognosis. Being initially recognized as a co-receptor involved in HIV infection, numerous CXCR4-targeting ligands and antagonists, including small molecules, peptides and biologics have been identified over the past decades. While only few of them have been used in the context of cancer therapies, recent biotechnological advancements using CXCR4 as a molecular target are showing significant potential to revolutionize future cancer therapies. Therefore, this review highlights the biotechnological innovations developed for cancer therapy and diagnosis by targeting the chemokine receptor CXCR4. It also discusses future perspectives on emerging therapeutic strategies, ranging from the use of small molecule inhibitors that block receptor signaling to cutting-edge nanocarriers designed for the targeted delivery of innovative drugs and proteins into cancer stem cells, aiming at cell-selective precision nanomedicines.